Redox-active rotaxanes and catenanes for anion sensing - Evans, N (2011)
This thesis is concerned with the synthesis and study of novel anion templated rotaxanes and catenanes for electrochemical anion sensing, as well as interlocked structures that possess different anion binding properties, higher-order topologies and the ability to undergo molecular motion. Chapter One provides an introduction to anion recognition and the preparation of interlocked structures. A short summary of fundamental aspects of supramolecular chemistry is followed by detailed surveys of current approaches to anion binding and sensing, as well as the templated synthesis of rotaxanes and catenanes. Chapter Two describes the preparation of rotaxanes and catenanes appended with ferrocene to allow for electrochemical anion sensing. The anion recognition properties of a [2]rotaxane and a [2]catenane, as investigated by ¹H NMR spectroscopy and electrochemical methods, are presented. The utilization of a ferrocene-appended macrocycle in the construction of surface confined anion templated rotaxanes and catenanes is also discussed. Chapter Three reports the work carried out to achieve electrochemical anion sensing by the incorporation of redox-active groups into the integral structures of interlocked structures. The syntheses of a bis-stoppered 1, 2, 3, 4, 5-pentaphenylferrocene [2]rotaxane and a ferrocene containing [3]rotaxane are presented, along with their subsequent anion recognition studies. In addition, attempts to incorporate ferrocene into the macrocyclic components of rotaxanes and catenanes are outlined. Chapter Four details further investigations into the use of interlocked structures to achieve anion recognition. Doubly-charged [2]catenanes able to bind anions in aqueous solvent media, as well as the incorporation of alternative anion binding motifs into interlocked architectures are reported. The exploitation of anion templated synthesis to allow for the construction of higher order structures (including [3]catenanes, a “handcuff” catenane and a Janus [2]rotaxane), as well as a [2]catenane system with anion controlled molecular motion is also described. Chapter Five presents the experimental procedures and characterization data relating to the compounds prepared in Chapters Two, Three and Four. Chapter Six summarizes the main conclusions of the work contained within this thesis. Supplementary experimental information relating to titration protocols, investigations into self-assembled monolayers (SAMs) and crystallographic data are provided in Appendices I, II and III.